Analisis Produksi Dan Pendapatan Sebelum Dan Sesudah Penggunaan Combine Harvester Di Kabupaten Pidie Jaya - M Murtadha; I Ismayani; S Safrida (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2019)
The Government through the APBN agricultural mechanization packaged by The Directorate General of Food Crops has provided post-harvest facilities assistance in rice-producing areas since 2012, including Combine Harvester which is expected to help post-harvest rice handling. This research was conducted with the aims to know differences in rice farming income before and after using Combine Harvester, and determine the efficiency of rice farming using Combine Harvester in Pidie Jaya Distrct. The results showed there were differences in income of rice farmers before and after using Combine Harvest where there was an increase in income after using Combine Harvest. Allocative efficiency of rice farming uses factors of seed production, KCl, SP36, Urea, NPK Fertilizer, Pesticides and Labor Costs are not efficient. However, in economic efficiency factors of KCl, SP36, Urea Fertilizer and labor costs are already efficient while the seed factor, NPK fertilizer and pesticide are not efficient